Pilot Study of Animal Assisted Therapy Provided in a Student Run Pro Bono Clinic - Fralinger, Colleen; Coker Bolt, Patty; Bennett, Cathy; Craig, Suzanne (Journal of Student-Run Clinics, 2023)
Background: Animal assisted therapy (AAT) is therapeutic intervention designed to help patients engage in meaningful life activities.1 Therapy dogs are used in healthcare settings to engage patients in motion, self-care, mental health, motivation, social responses, pain management, and fine motor skills.2 While there is research on the benefits of AAT with children and adults in inpatient settings, there is a lack of information on the benefits and satisfaction of AAT in student-run free clinics (SRFC). Methods: Occupational therapy (OT) students, volunteer clinicians, trained therapy dog teams, and patients receiving OT services at the Community Aid, Relief, Education & Support (CARES) SRFC participated in a pilot AAT program. All participants completed a specially designed survey via REDcap immediately following AAT sessions. Surveys focused on the patient’s pain and stress levels, benefits of AAT, and patient satisfaction. Results: Ten patients participated in the AAT pilot program alongside thirty-seven students and 4 therapy dog teams. 100% of patients responded therapy dogs helped them reach their goals, 93.8% of handlers and clinicians agreed the dog was a valuable addition to therapy sessions, and 100% of OT students agreed AAT is an important tool for therapists to use in clinical settings. 67.6% of patients reported a decrease in stress and 41.2% of patients who were experiencing pain reported a decrease in symptoms. Students, handlers, and clinicians reported benefits with AAT including range of motion (79.7%), fine motor skills (68.1%), and motivation (68.1%). Conclusion: AAT was successfully integrated into CARES SRFC based on feedback and data collected from participants. AAT had a visible impact on patients, students, handlers, and clinicians. Future research on the use of AAT in a SRFC should include a larger sample size and consider how to better define the specific impact of AAT on populations and conditions commonly seen in a SRFC.